DAMAR KURUNG CRAFTWORKS FOR GEOMETRICAL THINKING - Risywandha, Ihmah (Ethnomathematics Journal, 2024)
Damar kurung is one of the art works of Gresik Regency and has become a local cultural asset. From the making process to the use of the damar kurung, many features, objects, and activities can be identified as having mathematical elements. The present study is aimed at identifying mathematical objects and phenomena in the damar kurung that be used as instructional media to develop the five levels of geometrical thinking abilities with the different characteristics of learning achievements in each level. The study is qualitative research with the descriptive method. Data were collected by literary studies. Research results show that mathematical concepts found in the damar kurung that can be used as instructional media for developing geometrical thinking abilities are, among others, for Level 0:  triangle and square flat shapes and angles and lines; for Level 1: side and space diagonals and parallelism; for Level 2: two parallel lines cut by a transversal line, Phytagoras theorm, and surface areas and volumes of cubes; for Level 3: lengths of side and space diagonals; and Level 4: distances among points, points to lines, points to spaces, lines to lines, and among spaces. These mathematical concepts are in a match with the learning outcomes of the Phase D in the National Curriculum.